Use of xylometazoline in hospitalised infants: is it safe? A retrospective cohort study. Issue 1 (28th September 2022) - van Stralen, Karlijn J; van Tol, Joyce E; de Wildt, Saskia N; Becker, Matthijs L; van Houten, Marlies A
Abstract : Objective: When infants suffer from nasal congestion, xylometazoline spray or drops can be effective to facilitate breathing and drinking. However, case reports on side effects have resulted in international warnings regarding use of xylometazoline in infants. Nevertheless, the incidence of these side effects in hospitalised infants is unknown. Design: Retrospective cohort study. Setting: Teaching hospital between 2017 and 2021. Patients: Infants under 2 years of age. Exposure: Receiving either saline-only (unlimited frequency, concentration 0.9%) or in combination with xylometazoline (maximum three times daily, concentration 0.025%). Main outcome measures: Predefined potential side effects (events), including among others apnoea, nausea, bradycardia, cyanosis and nosebleeds, were extracted from patient records, and the probability to be caused by saline only or xylometazoline–saline was determined using the ADR Probability Scale. Results: We included 898 admitted children during 1285 treatment episodes who received saline with or without xylometazoline. 26 events occurred in the saline-only group (incidence 20.0/100 treatment episodes), and 117 events occurred in the xylometazoline saline group (incidence of 10.5/100 treatment episodes), which was significantly lower (OR 0.47 95% CI 0.29 to 0.75, p=0.002). No definite linked or life-threatening events were found. Three nosebleeds had a probable link to the use of xylometazoline–saline, and all other events could only possibly be linked to saline-only or xylometazoline saline use. The incidence of all events was higher in the saline-only group as compared with the xylometazoline saline group, except nausea, which had a similar occurrence (p=0.65). Results were very similar across (gestational) age groups, gender and reasons for admission. Conclusion: The use of low-dose xylometazoline seems to be safe in hospitalised infants. Abstract : Xylometazoline spray or drops were evaluated for safety when used for nasal decongestion in infants less than 2 years of age in a Dutch study - and the study concludes they appear to be safe.